A Multifaceted Approach to Doxing Offenses: Assessing Legal Responses Drawing from National, Islamic Criminal, and Human Rights Frameworks - Abdul Syatar; Alamsyah Halim; Muhammad Fazlurrahman Syarif (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
This study examines the phenomenon of document tracing, commonly referred to as doxing, as a growing legal and ethical challenge in Indonesia. It aims to analyze how national law, Islamic criminal law, and human rights frameworks respond to doxing, particularly in safeguarding privacy and protecting individuals from reputational and security harms. Employing a qualitative–empirical design, the research combines document analysis with case studies through a comparative approach. Data were collected via semi-structured interviews with academics, religious scholars, and activists, complemented by observation and a review of relevant laws, policies, and real-life instances of doxing. Triangulation was used to ensure credibility and comprehensiveness. The findings reveal that Indonesia has addressed doxing primarily through the Information and Electronic Transactions (ITE) Law, the Personal Data Protection Law, and provisions in the Criminal Code. From the perspective of Islamic criminal law, doxing is classified as al-jarā’im al-mahẓūrāt (prohibited acts) that violate privacy, with punishments potentially falling under hudūd or ta‘zīr. In both legal systems, doxing is recognized as a violation of fundamental human rights, particularly the right to privacy and dignity. Unlike prior studies that focus narrowly on either legal or technological dimensions, this research integrates national law, Islamic jurisprudence, and human rights principles into a unified analysis. It highlights the role of maqāṣid al-sharī‘a in developing privacy protections and in bridging classical legal concepts with contemporary digital realities. The study suggests that strengthening legal frameworks through both statutory reform and Islamic jurisprudential interpretation can provide more equitable protection for citizens. These findings contribute to broader debates on digital ethics, privacy, and the harmonization of religious and secular legal systems in addressing emerging cybercrimes.